New methods of evaluating physical demand at work areas - Elola, Luis Navarro (Technovation)
The manufacturer's requirement of increasing productivity results in the need to design work stations that are increasingly more effective and specialized. However, this procedure can bring about an overloading of the worker, a lack of motivation, and, consequently, a reduction in productivity. Ergonomics adapts the work station to the worker with the object of improving his welfare and satisfaction at his post. One aspect that this science concerns itself with is the evaluation of physical demands connected to productive tasks. Mechanical movements are also studied in order to perform tasks efficiently. We here propose a new method of physical demand analysis that determines the risk factor for muscular skeletal lesion. This method uses, as a base, the system of predetermined times. MTM-UAS. It includes a computer system that allows us to easily analyse the operations at a work station and generates charts similar to those of UAS, but, instead of times, it measures the quantity of mechanical work necessary for each movement. The information that the method provides can be used by different divisions within companies in making decisions about improvements at work stations.